Pemaknaan Bahasa dalam Konteks Komunikasi Antarbudaya: Sebuah Pendekatan Teoretis - M.Rizky Syahrer Syahputra (JURNAL ILMIAH NUSANTARA, 2025)
In the era of globalization marked by high mobility and increasingly intense intercultural interactions, language plays a crucial role as a means of conveying messages and as a marker of cultural identity. This article aims to examine the meaning of language in the context of intercultural communication through a theoretical approach. By examining major theories such as linguistic relativity, intercultural communication competence, and cross-cultural communication models, this article highlights how differences in perception, symbols, and language structures affect the effectiveness of communication between individuals from different cultural backgrounds. This study also emphasizes the importance of cultural sensitivity and linguistic awareness in reducing miscommunication and increasing intercultural understanding. The results of the study indicate that the meaning of language is not only determined by linguistic structures alone, but also by the socio-cultural context in which the language is used. These findings provide theoretical contributions to the development of intercultural communication studies and become an important basis for inclusive and effective communication practices amidst global diversity.